2016
DOI: 10.1111/apt.13745
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of mortality in patients with spontaneous bacterial peritonitis

Abstract: We developed and validated a predictive model of mortality that includes serum urea, blood leucocyte count, Child-Pugh score and mean arterial pressure in high-risk patients with spontaneous bacterial peritonitis. These findings may help to identify patients who would benefit from additional therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
(132 reference statements)
3
23
0
Order By: Relevance
“…The lower mortality rate of our study might be due to the patients being younger (57 vs. 62 years) and the absence of patients with hepatocellular carcinoma. In another study, Poca et al found the in-hospital mortality rate of SBP as 28% and showed that mean arterial pressure, serum leukocyte count, and serum urea levels were related to mortality [27]. Similarly, our study showed that mortality was higher in patients with high serum leukocyte counts.…”
Section: Discussionsupporting
confidence: 79%
“…The lower mortality rate of our study might be due to the patients being younger (57 vs. 62 years) and the absence of patients with hepatocellular carcinoma. In another study, Poca et al found the in-hospital mortality rate of SBP as 28% and showed that mean arterial pressure, serum leukocyte count, and serum urea levels were related to mortality [27]. Similarly, our study showed that mortality was higher in patients with high serum leukocyte counts.…”
Section: Discussionsupporting
confidence: 79%
“…Severity of liver dysfunction[ 42 , 54 , 56 , 61 , 102 ] including the Child-Pugh score or model for end-stage liver disease (MELD) score has been reported as a predictive factor, but few studies have not found an association of MELD score and the incidence of SBP[ 103 ] in patients with LC and refractory ascites. The MELD score does not include some clinical variables that are evaluated in the Child-Pugh score[ 104 , 105 ]. A PMN count[ 42 , 102 ] and a low protein concentration (< 1.5 g/dL) in the ascitic fluid, which may be related to decreased opsonic activity in the ascitic fluid[ 26 , 54 , 56 ], have also been reported as predictive factors, but the evidence for ascitic fluid protein is not conflicting[ 106 ].…”
Section: Spontaneous Bacterial Peritonitismentioning
confidence: 99%
“…Predictors of mortality in SBP include severe underlying liver disease with a high Child-Pugh[ 48 , 52 , 64 , 96 , 100 , 102 , 104 , 105 , 120 - 122 ] or MELD score[ 47 , 48 , 52 , 104 , 121 - 123 ], renal impairment[ 16 , 52 , 54 , 64 , 65 , 96 , 100 , 124 , 125 ] such as HRS, and onset of severe sepsis[ 96 ]. Some studies did not find differences in the mortality of nosocomial and community-acquired SBP[ 63 ]; others have reported increased mortality in nosocomial compared with community-acquired SBP, which was correlated with the involvement of drug-resistant bacteria[ 4 , 21 , 63 , 65 ].…”
Section: Spontaneous Bacterial Peritonitismentioning
confidence: 99%
“…Risk factors could be integrated into predictive models of mortality in individuals with SBP so as to further help identify patients in need of more aggressive therapeutic strategies from the very start of the infective process[ 81 ].…”
Section: Future Perspectivesmentioning
confidence: 99%